Penerapan Beyond Budgeting : Kajian Kesiapan Dan Dampaknya Terhadap Kinerja Pemkot Surakarta - Sugiarti; Ariefah Yulandari; Sugiyarmasto; Narika Selvy Oktavia (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the readiness and potential impact of implementing beyond budgeting on the performance of the Surakarta City Government. This study addresses the limitations of traditional budgeting systems in responding to dynamic environmental changes and increasing demands for transparency and accountability. The purpose of this study is to explore the organization's readiness to adopt beyond budgeting principles as an alternative management control system in the public sector. This study uses a qualitative descriptive approach with a case study method. Data were collected through interviews, observations, and documentation, and analyzed using a SWOT analysis based on twelve beyond budgeting principles. The results indicate that the Surakarta City Government has strong potential to implement beyond budgeting, supported by strengths such as customer orientation, transparency, accountability, and effective use of technology. However, several challenges remain, including coordination issues, budget constraints, and social issues. Overall, beyond budgeting can increase flexibility, efficiency, and adaptability in financial management, thereby improving public service performance and governance quality. Keywords : Beyond budgeting, sektor publik, manajemen keuangan, kesiapan organisasi, analisis SWOT